Triggerless data acquisition pipeline for Machine Learning based statistical anomaly detection - Grosso Gaia; Lai Nicolò; Migliorini Matteo; Pazzini Jacopo; Triossi Andrea; Zanetti Marco; Zucchetta Alberto (EPJ Web of Conferences, 2024)
This work describes an online processing pipeline designed to identify anomalies in a continuous stream of data collected without external triggers from a particle detector. The processing pipeline begins with a local reconstruction algorithm, employing neural networks on an FPGA as its first stage. Subsequent data preparation and anomaly detection stages are accelerated using GPGPUs. As a practical demonstration of anomaly detection, we have developed a data quality monitoring application using a cosmic muon detector. Its primary objective is to detect deviations from the expected operational conditions of the detector. This serves as a proof-of-concept for a system that can be adapted for use in large particle physics experiments, enabling anomaly detection on datasets with reduced bias.